Negative electrode active material for lithium-ion secondary batteries

Nitrogen-doped carbon particles produced by firing polybenzimidazole at high temperatures address the limitations of existing materials by offering high discharge capacity, durability, and fast charging capabilities for lithium ion secondary batteries.

JP7599196B2Active Publication Date: 2024-12-13JAPAN ADVANCED INST OF SCI & TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2020145388
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-31
Publication Date
2024-12-13
Estimated Expiration
2040-08-31

AI Technical Summary

Technical Problem

Existing nitrogen-doped carbon materials exhibit low redox activity and discharge capacity, and lack durability and high-speed charging properties for lithium ion secondary batteries.

Method used

Production of nitrogen-doped carbon particles with a nitrogen atom content of 15% by mass or more, achieved by firing polybenzimidazole at 550 to 1500°C in a nitrogen gas atmosphere, resulting in carbon with high discharge capacity and excellent durability and high-speed charging properties.

Benefits of technology

The nitrogen-doped carbon particles demonstrate high discharge capacity, excellent durability against charging and discharging, and enable fast charging, enhancing the performance of lithium ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007599196000013
    Figure 0007599196000013
  • Figure 0007599196000014
    Figure 0007599196000014
  • Figure 0007599196000015
    Figure 0007599196000015
Patent Text Reader

Abstract

To provide a nitrogen-doped carbon having high discharge capacity, being excellent in durability for discharge and charge, and being excellent in a high-speed charge property of being capable of charge in a short time, a negative-electrode active material for a lithium-ion secondary battery containing the nitrogen-doped carbon, and a lithium-ion secondary battery having a negative electrode including the negative-electrode active material for the lithium-ion secondary battery.SOLUTION: A nitrogen-doped carbon particle has a content of nitrogen atoms of 15 mass% or more. A method for producing the nitrogen-doped carbon particle comprises firing polybenzimidazole at a temperature of 550 to 1500°C in a nitrogen gas-containing atmosphere. A negative-electrode active material for a lithium-ion secondary battery contains the nitrogen-doped carbon particle. The lithium-ion secondary battery has a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the negative electrode including the negative-electrode active material.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a negative electrode active material for a lithium ion secondary battery. More specifically, the present invention relates to a negative electrode active material for a lithium ion secondary battery, nitrogen-doped carbon particles suitable for use in the negative electrode active material for a lithium ion secondary battery and a method for producing the same, and a lithium ion secondary battery having a negative electrode containing the negative electrode active material for a lithium ion secondary battery. [Background technology]

[0002] Nitrogen-doped carbon is used as an electrochemical catalyst in reactions such as redox reactions and oxygen evolution reactions, a material for supercapacitors, etc. It is generally believed that the higher the nitrogen content in nitrogen-doped carbon, the higher the redox activity of the nitrogen-doped carbon (see, for example, paragraph

[0002] of Patent Document 1).

[0003] As a method for producing nitrogen-doped carbon with a high nitrogen content, a method for producing nitrogen-containing carbon has been proposed, which includes the steps of using a sintering vessel made of quartz to sinter carbon in an atmosphere containing carbon dioxide gas, lowering the internal temperature of the sintering vessel to 100°C or lower, and replacing the internal atmosphere of the sintering vessel with an ammonia-containing gas atmosphere and sintering the carbon (see, for example, claim 1 of Patent Document 1).

[0004] However, since the nitrogen content in the nitrogen-containing carbon obtained by the above-mentioned method for producing nitrogen-containing carbon is about 1.5% by weight (for example, see paragraph

[0013] and FIG. 2 of Patent Document 1), the redox activity of the nitrogen-containing carbon cannot be said to be particularly high, and improvement in the discharge capacity is desired.

[0005] In recent years, there has been a demand for the development of nitrogen-doped carbon that has a high discharge capacity, excellent durability against charging and discharging, and excellent high-speed charging ability that enables charging in a short period of time. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2015-67487 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in view of the above-mentioned conventional techniques, and an object of the present invention is to provide nitrogen-doped carbon which has a high discharge capacity, excellent durability against charging and discharging, and excellent high-speed charging ability enabling charging in a short time, a method for producing the same, a negative electrode active material for a lithium ion secondary battery which contains the nitrogen-doped carbon, and a lithium ion secondary battery having a negative electrode which contains the negative electrode active material for a lithium ion secondary battery. [Means for solving the problem]

[0008] The present invention relates to (1) Nitrogen-doped carbon particles having a nitrogen atom content of 15 mass% or more; (2) A method for producing the nitrogen-doped carbon particles according to the above (1), comprising calcining polybenzimidazole at a temperature of 550 to 1500° C. in a nitrogen gas-containing atmosphere. (3) A negative electrode active material for a lithium ion secondary battery, comprising the nitrogen-doped carbon particles according to (1) above; and (4) A lithium ion secondary battery having a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the negative electrode comprising the negative electrode active material for lithium ion secondary batteries according to (3) above. Regarding.

[0009] In the present invention, nitrogen-doped carbon means carbon that is doped (contains) nitrogen. Effect of the Invention

[0010] According to the present invention, there are provided nitrogen-doped carbon which has a high discharge capacity, excellent durability against charging and discharging, and excellent high-speed charging property that enables charging in a short time, a method for producing the same, a negative electrode active material for a lithium ion secondary battery containing the nitrogen-doped carbon, and a lithium ion secondary battery having a negative electrode containing the negative electrode active material for a lithium ion secondary battery. [Brief description of the drawings]

[0011] [Figure 1] 4(a) to 4(c) are powder X-ray diffraction patterns of the nitrogen-doped carbon particles obtained in Examples 1 to 3, respectively. [Diagram 2] 1 is a scanning electron microscope photograph showing the results of energy dispersive X-ray analysis of the nitrogen-doped carbon particles obtained in Example 3. [Diagram 3] FIG. 1(a) is a scanning electron microscope photograph showing the results of energy-dispersive X-ray analysis of the carbon contained in the nitrogen-doped carbon particles obtained in Example 3, FIG. 1(b) is a scanning electron microscope photograph showing the results of energy-dispersive X-ray analysis of the nitrogen contained in the nitrogen-doped carbon particles, and FIG. 1(c) is a scanning electron microscope photograph showing the results of energy-dispersive X-ray analysis of the oxygen contained in the nitrogen-doped carbon particles. [Figure 4] 4(a) and 4(b) are transmission electron microscope photographs of the nitrogen-doped carbon particles obtained in Example 3. [Diagram 5] 1 is a graph showing the results of energy dispersive X-ray analysis of the nitrogen-doped carbon particles obtained in Example 3. [Figure 6] 6(a) is a graph showing the results of X-ray photoelectron spectroscopy of the nitrogen-doped carbon particles obtained in Example 3, and (b) is a graph in which the peak based on N1s is enlarged in the graph showing the results of X-ray photoelectron spectroscopy of the nitrogen-doped carbon particles shown in FIG. 6(a). [Figure 7]1(a) is a graph showing the relationship between the charge transfer resistance at the interface between the electrolyte and the electrode at frequencies of 1 MHz to 100 mHz in the nitrogen-doped carbon particles obtained in Example 3, and (b) is a graph showing the results of cyclic voltammetry measurements. [Figure 8] Graph (a) shows the measurement results of the current value when cyclic voltammetry of a negative electrode half-cell using the nitrogen-doped carbon particles obtained in Example 3 was examined at voltages of 0.1 V / s, 0.3 V / s, 0.5 V / s, 0.7 V / s, or 1.0 V / s, and graph (b) shows the relationship between the scan rate and peak current in the cyclic voltammetry of the negative electrode half-cell. [Figure 9] Graph A shows the relationship between the number of charge / discharge cycles of a negative electrode half-cell and the discharge capacity, and graph B shows the relationship between the number of charge / discharge cycles of a negative electrode half-cell and the charge / discharge efficiency (Coulomb efficiency). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] As described above, the nitrogen-doped carbon particles of the present invention have a nitrogen atom content of 15% by mass or more. The nitrogen atom content in the nitrogen-doped carbon particles is a value measured based on the method described in the following examples. The nitrogen-doped carbon particles of the present invention have a nitrogen atom content of 15% by mass or more, preferably 15 to 25% by mass, and more preferably 18 to 25% by mass, and therefore have a high discharge capacity, excellent durability against charge and discharge, and excellent high-speed chargeability that allows charging in a short time.

[0013] The nitrogen-doped carbon particles of the present invention can be produced, for example, by firing polybenzimidazole at a temperature of 550 to 1500° C. in a nitrogen gas-containing atmosphere.

[0014] [Polybenzimidazole] Polybenzimidazoles have the formula:

[0015] [ka]

[0016] The polybenzimidazole is a polymer having a repeating unit represented by the formula: In addition to the repeating unit, the polybenzimidazole may contain other repeating units than the repeating unit as long as the object of the present invention is not hindered. Polybenzimidazole is commercially available and can be prepared as follows.

[0017] As a raw material for polybenzimidazole, for example, 3,4-diaminobenzoic acid dihydrochloride can be used. 3,4-Diaminobenzoic acid dihydrochloride can be easily prepared by reacting 3,4-diaminobenzoic acid with hydrochloric acid.

[0018] Polybenzimidazole can be prepared, for example, by heating 3,4-diaminobenzoic acid dihydrochloride in an inert gas atmosphere in the presence of polyphosphoric acid at a temperature of about 80 to 150°C until polybenzimidazole is produced. Examples of inert gases include nitrogen gas and argon gas, but the present invention is not limited to these examples. The produced polybenzimidazole may be washed, dried, and pulverized to have a desired particle size, if necessary.

[0019] From the viewpoint of obtaining nitrogen-doped carbon having a high discharge capacity, excellent durability against charge and discharge, and excellent high-speed chargeability that can be charged in a short time, the number average molecular weight of the polybenzimidazole is preferably 2000 to 100,000, more preferably 3000 to 100,000 when it does not have a crosslinked structure, and is preferably 2000 to 1,000,000, more preferably 3000 to 1,000,000 when it has a crosslinked structure.

[0020] The number average molecular weight of polybenzimidazole is a value measured by gel permeation chromatography (GPC) under the following measurement conditions.

[0021] [Measurement conditions] Equipment: Showa Denko Co., Ltd., product name: Shodex-101 Injection concentration: 0.01% by mass ·Injection volume: 100μL ·Flow rate: 1mL / min Solvent: N,N-dimethylformamide Column: Showa Denko K.K., product name: Shodex KD-803 and product name: Shodex KD-804 Column temperature: 40℃ Standard: Polymethylmethacrylate

[0022] [Nitrogen-doped carbon particles] Next, the polybenzimidazole is baked to obtain nitrogen-doped carbon particles. When baking the polybenzimidazole, it is preferable to pulverize the polybenzimidazole in advance in order to increase the baking efficiency of the polybenzimidazole. The particle size of the pulverized polybenzimidazole is not particularly limited, but is preferably 1 mm or less, more preferably 500 μm or less, and even more preferably 300 μm or less from the viewpoint of increasing the baking efficiency of the polybenzimidazole.

[0023] When polybenzimidazole is sintered, for example, an electric furnace or the like can be used. The atmosphere when sintering polybenzimidazole is a nitrogen gas-containing atmosphere from the viewpoint of efficiently producing nitrogen-doped carbon particles. The nitrogen gas atmosphere is ideally a nitrogen gas atmosphere, but the nitrogen gas atmosphere may contain, for example, an inert gas such as argon gas, air, oxygen gas, carbon dioxide gas, etc., within a range that does not impede the object of the present invention.

[0024] The temperature rise rate during the baking of polybenzimidazole is not particularly limited. The temperature rise rate during the baking of polybenzimidazole may be changed stepwise or may be maintained constant. The baking temperature of polybenzimidazole is preferably 550 to 1500°C, more preferably 600 to 1300°C, and even more preferably 600 to 1100°C, from the viewpoint of efficiently producing nitrogen-doped carbon that is excellent in durability against charging and discharging and has excellent high-speed charging ability that can be charged in a short time.

[0025] The baking time of polybenzimidazole cannot be determined in general because it varies depending on the baking temperature of polybenzimidazole, but is usually about 0.5 to 6 hours. After baking the polybenzimidazole, the baked polybenzimidazole may be allowed to cool to a temperature of preferably 40°C or less, more preferably room temperature. The baking temperature of polybenzimidazole can be measured using a thermocouple.

[0026] In this manner, nitrogen-doped carbon particles can be obtained. If the obtained nitrogen-doped carbon particles are aggregated, the nitrogen-doped carbon particles may be disintegrated using a pin mill, a hammer mill, or the like, as necessary.

[0027] In the nitrogen-doped carbon particles of the present invention, the presence of a (002) plane peak is observed by X-ray diffraction, but since the (002) plane peak is broad, it is determined that the particles are amorphous carbon.

[0028] In addition, when the nitrogen-doped carbon particles are observed with a transmission electron microscope, it is found that the nitrogen-doped carbon particles have macropores with a pore size exceeding 50 nm and mesopores with a pore size in the range of 2 to 50 nm. Therefore, since the nitrogen-doped carbon particles have macropores and mesopores, it is considered that they have excellent lithium ion diffusibility.

[0029] X-ray photoelectron spectroscopy (XPS) of the nitrogen-doped carbon particles revealed that the nitrogen-doped carbon particles had the formula (Ia): [ka]

[0030] A compound having graphitic nitrogen (graphite-type nitrogen) represented by formula (Ib):

[0031] [ka]

[0032] pyridine represented by formula (Ic):

[0033] [ka]

[0034] and pyrroles of formula (Id):

[0035] [ka]

[0036] From this, it is considered that the nitrogen-doped carbon particles contain the compounds represented by the formulas (Ia) to (Id) that are generated by decomposition of the polybenzimidazole used as the raw material of the nitrogen-doped carbon particles by baking.

[0037] It has been confirmed in the following Examples that the spacing between crystal planes of the nitrogen-doped carbon particles of the present invention is 0.35 to 0.37 nm, which is wider than the spacing between crystal planes of graphite.

[0038] The average particle diameter of the nitrogen-doped carbon particles when observed with a transmission electron microscope is usually within the range of 50 nm to 10 μm. The average particle diameter of the nitrogen-doped carbon particles is calculated by randomly selecting 100 nitrogen-doped carbon particles from an image taken with a scanning electron microscope, calculating the average values ​​of the vertical axis and horizontal axis of each nitrogen-doped carbon particle, summing the average values ​​for the 100 nitrogen-doped carbon particles, and dividing the sum by 100.

[0039] [Negative electrode active material for lithium ion secondary batteries] The negative electrode active material for lithium ion secondary batteries of the present invention contains the nitrogen-doped carbon particles. The negative electrode active material for lithium ion secondary batteries of the present invention may be composed of only the nitrogen-doped carbon particles, or may contain other negative electrode active materials within a range that does not impede the object of the present invention. Examples of other negative electrode active materials include powders of carbon materials such as graphite, graphite, and coke, but the present invention is not limited to only these examples.

[0040] [Lithium-ion secondary battery] The lithium ion secondary battery of the present invention has the same structure as commonly used lithium secondary ion batteries.

[0041] The lithium ion secondary battery of the present invention usually has a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte. The shape of the lithium ion secondary battery may be, for example, a cylindrical type or a laminated type, but the present invention is not limited to these examples.

[0042] When the lithium ion secondary battery of the present invention is, for example, a CR2025 lithium ion secondary battery, the negative electrode, the separator, and the non-aqueous electrolyte are housed in a case. In the following, an embodiment in which the lithium ion secondary battery is a CR2025 lithium ion secondary battery will be described, but the present invention is not limited to only this embodiment.

[0043] The case used in the CR2025 lithium-ion secondary battery is hollow, has an opening, and also serves as a positive electrode container. A lid is provided at the opening of the case, and the lid also serves as a negative electrode lid. A gasket is provided between the case and the lid to maintain an insulating and sealed state between the case and the lid. An electrode and a non-aqueous electrolyte are accommodated in the space between the case and the lid.

[0044] (1) Electrode The electrodes include a positive electrode, a separator, and a negative electrode, arranged in that order. The positive electrode is in contact with the inner surface of the case, and the negative electrode is in contact with the inner surface of the lid.

[0045] The positive electrode may be the same as a positive electrode used in a commonly used lithium secondary ion battery, and the present invention is not limited by the composition and structure of the positive electrode.

[0046] The positive electrode can be produced, for example, by mixing a positive electrode active material, a conductive material, and a binder in a predetermined ratio, adding a solvent, and optionally activated carbon, a viscosity adjusting additive, and the like, to the resulting mixture, kneading the resulting mixture to prepare a positive electrode composite paste, applying the paste to the surface of a current collector, and optionally press-molding and drying the paste.

[0047] Representative examples of the positive electrode active material include lithium and lithium-manganese composite oxides, but the present invention is not limited to these examples. Examples of the conductive material include carbon black such as acetylene black, natural graphite, artificial graphite, and expanded graphite, but the present invention is not limited to these examples. Examples of the binder include polyvinylidene fluoride (PVDF), 1-methyl-2-pyrrolidone (NMP), polytetrafluoroethylene (PTFE), fluororubber, and ethylene propylene diene rubber, but the present invention is not limited to these examples. Examples of the solvent include N-methyl-2-pyrrolidone, but the present invention is not limited to these examples.

[0048] The negative electrode is made of the negative electrode active material of the present invention. The negative electrode can be produced, for example, by mixing the negative electrode active material of the present invention with a binder, adding a solvent to the resulting mixture to prepare a paste-like negative electrode mixture, applying the negative electrode mixture to the surface of a metal foil collector such as copper, drying it, and press-molding it as necessary, followed by drying.

[0049] The negative electrode active material of the present invention is used, but powders such as graphite and carbon black may be included as necessary. Examples of binders include polyvinylidene fluoride (PVDF), 1-methyl-2-pyrrolidone (NMP), polytetrafluoroethylene (PTFE), fluorine rubber, and ethylene propylene diene rubber, but the present invention is not limited to these examples. Examples of solvents include N-methyl-2-pyrrolidone, but the present invention is not limited to these examples.

[0050] The separator is used between the positive electrode and the negative electrode. The separator separates the positive electrode and the negative electrode, holds the electrolyte, and forms a path for lithium ions to move between the positive electrode and the negative electrode. The separator can be a foil film of a polyolefin resin such as polyethylene or polypropylene, and the thin film has many micropores formed therein.

[0051] (2) Nonaqueous electrolyte Examples of the non-aqueous electrolyte include cyclic carbonates such as ethylene carbonate, diethylene carbonate, propylene carbonate, butylene carbonate, and trifluoropropylene carbonate; chain carbonates such as diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, and dipropyl carbonate; and ether compounds such as tetrahydrofuran, 2-methyltetrahydrofuran, and dimethoxyethane; however, the present invention is not limited to these examples.

[0052] The lithium ion secondary battery of the present invention has a high discharge capacity because a negative electrode containing the negative electrode active material for lithium ion secondary batteries of the present invention is used as the negative electrode active material, and has excellent properties such as excellent durability against charging and discharging because the decrease in discharge capacity is small even after 1,200 charge and discharge cycles, and excellent high-speed charging ability because it can be charged in a short time. EXAMPLES

[0053] Next, the present invention will be described in detail based on examples, but the present invention is not limited to these examples.

[0054] The physical properties measured in the following examples were measured according to the following methods. [Powder X-ray diffraction] Powder X-ray diffraction was performed using a powder / thin film X-ray diffractometer (Rigaku Corporation, product name: SmartLab) with CuKα radiation having a wavelength (λ) of 0.154 nm in the measurement range (2θ) of 10 to 80°.

[0055] [Energy Dispersive X-ray Analysis (EDS)] The measurement was carried out using a tabletop microscope (manufactured by Hitachi High-Technologies Corporation, product name: Miniscope (registered trademark) TM3030).

[0056] [Observation by transmission electron microscope (TEM)] Observation was carried out using a transmission electron microscope (Hitachi, Ltd., model number: H-7100, accelerating voltage: 100 kV).

[0057] [X-ray photoelectron spectroscopy (XPS)] X-ray photoelectron spectroscopy was performed using an X-ray photoelectron spectrometer (manufactured by Fison Instruments, product name: S-PROBE™ 2803).

[0058] [Cyclic Voltammetry] Using a potentiostat (Biological), cyclic voltammetry was measured at room temperature with a frequency of 1 MHz to 100 mHz and an output of 10 mV. The potential range during cyclic voltammetry was 10 to 2100 mV, and the scan rate was adjusted to 0.1 mV / s.

[0059] [Charging and discharging] The negative half-cell was charged and discharged using a compact charge-discharge device (EC Frontier Co., Ltd., product number: ECAD-1000) with Li / Li ++ The potential difference was adjusted to 10 to 2100 mV.

[0060] Production Example 1 [Preparation of polybenzimidazole] (1) Preparation of 3,4-diaminobenzoic acid dihydrochloride 3 g (19.72 mmol) of 3,4-diaminobenzoic acid was placed in a beaker at room temperature, and 20 mL of methanol was added to the beaker, after which the contents of the beaker were stirred for about 1 hour.

[0061] Next, 3 mL of 10% hydrochloric acid was dropped into the beaker while stirring the contents of the beaker, and the contents of the beaker were then stirred for about 4 hours. The contents of the beaker were filtered through a Buchner funnel to remove unreacted precipitates, and the filtrate was collected.

[0062] The solvent (methanol) was removed from the filtrate obtained above using a rotary evaporator to recover a solid content, which was then dried under reduced pressure for 5 to 6 hours to obtain 3,4-diaminobenzoic acid dihydrochloride.

[0063] (2) Preparation of polybenzimidazole While introducing nitrogen gas into a 100 mL three-neck flask, 30 g of polyphosphoric acid was added to the flask under stirring, and the polyphosphoric acid was heated at 120° C. for 1 hour to remove moisture from the polyphosphoric acid.

[0064] Next, 1.32 g of the 3,4-diaminobenzoic acid dihydrochloride obtained above was added to the flask and stirred at a temperature of 120°C for 1 hour. Then, the temperature of the contents of the flask was raised to 200°C and the contents of the flask were left at that temperature with stirring for about 14 hours to obtain polybenzimidazole.

[0065] (3) Purification of polybenzimidazole The polybenzimidazole obtained above was added to distilled water in a beaker at room temperature and left for about 24 hours to dissolve the remaining unreacted 3,4-diaminobenzoic acid dihydrochloride in water, thereby purifying the polybenzimidazole. The number average molecular weight of the polybenzimidazole obtained above was 36,000.

[0066] Next, the polybenzimidazole was removed from the beaker, placed in a dryer, and dried for about 6 to 7 hours under reduced pressure at a temperature of 180° C. The dried polybenzimidazole was pulverized for 20 minutes at a rotation speed of 1430 rpm in a pulverizer (manufactured by Japan Analytical Industry Co., Ltd., product number: JF-300) to obtain a polybenzimidazole powder.

[0067] The polybenzimidazole powder obtained above was added to a 10% potassium hydroxide aqueous solution at room temperature, and after stirring for about 12 hours, the polybenzimidazole powder was thoroughly washed with deionized water.Then, the polybenzimidazole powder was filtered through a fluororesin (polytetrafluoroethylene) filter membrane with a pore size of 0.1 μm, and the obtained residue was placed in a dryer and dried at a temperature of 80° C. for about 12 hours to obtain purified polybenzimidazole.

[0068] Example 1 After replacing the atmosphere inside a programmable tubular electric furnace (manufactured by AS ONE Corporation, product number: TMF-300N) with nitrogen gas, a silica-alumina combustion boat (manufactured by AS ONE Corporation) containing 100 mg of the polybenzimidazole obtained above was placed in the electric furnace, and the polybenzimidazole was baked while continuously introducing nitrogen gas into the electric furnace.

[0069] The polybenzimidazole was calcined by heating the polybenzimidazole from room temperature to 750°C at a temperature increase rate of 5°C / min, and when the temperature reached 750°C, heating it at a temperature increase rate of 1°C / min to 800°C, maintaining the temperature at 800°C for 1 hour, and then cooling it to room temperature. The yield of the calcined product obtained was 72 mg, and it was confirmed that the yield was 72% by mass.

[0070] The fired product obtained above was ground in an agate mortar and pestle, then added to 30 mL of 10% hydrochloric acid, and ultrasonic waves were applied to the resulting mixture for 10 to 15 minutes to obtain a dispersion of fired product powder. The dispersion obtained above was filtered through a fluororesin (polytetrafluoroethylene) filter membrane with a pore size of 0.1 μm, placed in a dryer, and dried at a temperature of 80°C for about 12 hours to obtain nitrogen-doped carbon particles.

[0071] Example 2 After replacing the atmosphere inside a programmable tubular electric furnace (manufactured by AS ONE Corporation, product number: TMF-300N) with nitrogen gas, a silica-alumina combustion boat (manufactured by AS ONE Corporation) containing 100 mg of the polybenzimidazole obtained above was placed in the electric furnace, and the polybenzimidazole was baked while continuously introducing nitrogen gas into the electric furnace.

[0072] The polybenzimidazole was calcined by heating the polybenzimidazole from room temperature to 950°C at a temperature increase rate of 5°C / min, and when the temperature reached 950°C, heating it at a temperature increase rate of 1°C / min to 1000°C, maintaining the temperature at 1000°C for 1 hour, and then cooling it to room temperature. The yield of the calcined product obtained was 71 mg, and it was confirmed that the yield was 71% by mass.

[0073] The fired product obtained above was ground in an agate mortar and pestle, then added to 30 mL of 10% hydrochloric acid, and ultrasonic waves were applied to the resulting mixture for 10 to 15 minutes to obtain a dispersion of fired product powder. The dispersion obtained above was filtered through a fluororesin (polytetrafluoroethylene) filter membrane with a pore size of 0.1 μm, placed in a dryer, and dried at a temperature of 80°C for about 12 hours to obtain nitrogen-doped carbon particles.

[0074] Example 3 After replacing the atmosphere inside a programmable tubular electric furnace (manufactured by AS ONE Corporation, product number: TMF-300N) with nitrogen gas, a silica-alumina combustion boat (manufactured by AS ONE Corporation) containing 100 mg of the polybenzimidazole obtained above was placed in the electric furnace, and the polybenzimidazole was baked while continuously introducing nitrogen gas into the electric furnace.

[0075] The polybenzimidazole was calcined by heating the polybenzimidazole from room temperature to 550°C at a temperature increase rate of 5°C / min, and when the temperature reached 550°C, heating it at a temperature increase rate of 1°C / min to 600°C, maintaining the temperature at 600°C for 1 hour, and then cooling it to room temperature. The yield of the calcined product obtained was 73 mg, and it was confirmed that the yield was 73% by mass.

[0076] The fired product obtained above was ground in an agate mortar and pestle, then added to 30 mL of 10% hydrochloric acid, and ultrasonic waves were applied to the resulting mixture for 10 to 15 minutes to obtain a dispersion of fired product powder. The dispersion obtained above was filtered through a fluororesin (polytetrafluoroethylene) filter membrane with a pore size of 0.1 μm, placed in a dryer, and dried at a temperature of 80°C for about 12 hours to obtain nitrogen-doped carbon particles.

[0077] Next, the powder X-ray diffraction patterns of the nitrogen-doped carbon particles obtained in Examples 1 to 3 are shown in Figure 1. From the results shown in Figure 1, the Miller indices of the nitrogen-doped carbon particles are (002), and the broad peak indicates that amorphous carbon is produced. In addition, the Bragg equation: nλ=2dsinθ (In the formula, n is a positive integer, λ is the wavelength of the X-ray, d is the spacing between the crystal planes, and θ is the angle between the crystal planes and the X-ray.) The spacing between the crystal planes of the nitrogen-doped carbon particles calculated based on the above was 0.37 nm in Example 1, 0.36 nm in Example 2, and 0.35 nm in Example 3, all of which are larger than the spacing between the crystal planes of the graphite powder (0.33 nm).

[0078] Next, the nitrogen-doped carbon particles obtained in Example 3 were used to examine the following physical properties. [Energy Dispersive X-ray Analysis (EDS)] The results of energy dispersive X-ray analysis of the nitrogen-doped carbon particles are shown in Fig. 2. Fig. 2 is a graph showing the results of energy dispersive X-ray analysis of the nitrogen-doped carbon particles obtained in Example 3.

[0079] Energy dispersive X-ray analysis was also performed on the carbon, nitrogen and oxygen contained in the nitrogen-doped carbon particles. The results are shown in Figure 3. In Figure 3, (a) is a graph showing the results of energy dispersive X-ray analysis of the carbon contained in the nitrogen-doped carbon particles, (b) is a graph showing the results of energy dispersive X-ray analysis of the nitrogen contained in the nitrogen-doped carbon particles, and (c) is a graph showing the results of energy dispersive X-ray analysis of the oxygen contained in the nitrogen-doped carbon particles.

[0080] The results shown in Figures 2 and 3 show that carbon, nitrogen and oxygen are uniformly dispersed in the nitrogen-doped carbon particles.

[0081] Moreover, from the results shown in FIG. 2, it was confirmed that the particle size of the nitrogen-doped carbon particles was within the range of 50 nm to 10 μm.

[0082] [Observation by transmission electron microscope (TEM)] A transmission electron microscope photograph of the nitrogen-doped carbon particles is shown in Figure 4. From the transmission electron microscope photograph of the nitrogen-doped carbon particles shown in Figure 4(a), it can be seen that the nitrogen-doped carbon particles have macropores with a pore size exceeding 50 nm and mesopores with a pore size in the range of 2 to 50 nm. It is believed that the macropores and mesopores of the nitrogen-doped carbon particles contribute to the diffusion and storage of lithium ions.

[0083] Furthermore, the transmission electron microscope photograph of the nitrogen-doped carbon particles shown in FIG. 4(b) reveals that the nitrogen-doped carbon particles have a layered structure and a structure in which carbon particles are interconnected, and are porous.

[0084] [Energy Dispersive X-ray Analysis (EDS)] A graph showing the results of energy dispersive X-ray analysis of the nitrogen-doped carbon particles is shown in Figure 5. Table 1 shows the contents of elements contained in the nitrogen-doped carbon particles obtained from the results of energy dispersive X-ray analysis of the nitrogen-doped carbon particles.

[0085] [Table 1]

[0086] As shown in Table 1, the nitrogen content in the nitrogen-doped carbon particles is 19.51% by mass, which is significantly higher than the nitrogen content of the nitrogen-containing carbon described in Patent Document 1, which is about 1.5% by mass (see FIG. 2 in Patent Document 1), and is therefore recognized to have excellent redox activity. Furthermore, when the nitrogen contents of the nitrogen-doped carbon particles obtained in Examples 1 and 2 were also examined, they were found to be 19.32% by mass and 20.25% by mass, respectively, and it is understood that these nitrogen-doped carbon particles have excellent redox activity, similar to the nitrogen-doped carbon particles obtained in Example 3.

[0087] [X-ray photoelectron spectroscopy (XPS)] The results of X-ray photoelectron spectroscopy of the nitrogen-doped carbon particles are shown in Figure 6. In Figure 6, (a) is a graph showing the results of X-ray photoelectron spectroscopy of the nitrogen-doped carbon particles, and (b) is a graph in which the peak based on N1s is enlarged in the graph showing the results of X-ray photoelectron spectroscopy of the nitrogen-doped carbon particles shown in Figure 6(a). In Figure 6(b), A is a graph of a compound having graphitic nitrogen (graphite-type nitrogen) represented by formula (Ia), B is a graph of pyridine represented by formula (Ib), C is a graph of pyrrole represented by formula (Ic), and D is a graph of an oxygen atom-containing pyridine compound represented by formula (Id).

[0088] From the results shown in Fig. 6(b), it was confirmed that the nitrogen-doped carbon particles contained 10.3 mass% of the compound having graphitic nitrogen (graphite-type nitrogen) represented by formula (Ia), 5.9 mass% of pyridine represented by formula (Ib), 0.6 mass% of pyrrole represented by formula (Ic), and 0.7 mass% of the oxygen-atom-containing pyridine compound represented by formula (Id). From this, it is considered that the polybenzimidazole used as the raw material for the nitrogen-doped carbon particles was decomposed by baking, and the compounds represented by formulas (Ia) to (Id) were generated.

[0089] [Cyclic Voltammetry] 80 g of nitrogen-doped carbon particles, 10 g of acetylene black, 10 g of polyvinylidene fluoride as a binder, and 400 g of N-methyl-2-pyrrolidone were mixed to a uniform composition, and the resulting slurry was applied to a copper foil (length: 20 mm, width: 100 mm, thickness: 20 μm) with a doctor blade, dried at a temperature of 80°C under reduced pressure for approximately 12 hours, and pressed with a roll to produce an electrode with a coating thickness of 0.06 mm after drying.

[0090] In order to incorporate the electrode obtained above into a CR2025 lithium ion secondary battery, a disk having a diameter of 15 mm was punched out, and the disk obtained above was used as the negative electrode, lithium foil was used as the counter electrode, a polypropylene separator (manufactured by Asahi Kasei Corporation, product name: Celgard 2500, thickness: 25 μm) was used as the separator, and an electrolyte obtained by dissolving LiPF6 in a solvent mixed with ethylene carbonate and diethylene carbonate in a mass ratio of 1:1 to a concentration of 1 M was used, and an anode half cell was assembled in an argon gas atmosphere. The obtained anode half cell was left at room temperature for 12 hours for stabilization.

[0091] The negative electrode half-cell obtained above was subjected to cyclic voltammetry, and the results are shown in Figures 7 and 8.

[0092] Fig. 7(a) is a graph showing the relationship of charge transfer resistance at the interface between the electrolyte and the electrodes at frequencies from 1 MHz to 100 mHz. In Fig. 7(a), A is a graph showing the relationship of charge transfer resistance at the interface between the electrolyte and the electrodes before cyclic voltammetry is performed, and B is a graph showing the relationship of charge transfer resistance at the interface between the electrolyte and the electrodes after cyclic voltammetry is performed.

[0093] The results shown in FIG. 7(a) indicate that when cyclic voltammetry was performed, the charge transfer resistance at the interface between the electrolyte and the electrode was reduced, indicating that a favorable interface was formed between the electrolyte and the electrode.

[0094] Fig. 7(b) is a graph showing the results of cyclic voltammetry measurement, in which reference numbers 1 to 5 indicate the results of cyclic voltammetry measurement for cycles 1 to 5, respectively.

[0095] From the results shown in FIG. 7(b), it can be seen that the current value increases significantly in the negative direction between 0 and 0.1 V, indicating that the lithiation of the electrode is progressing, and that the current value becomes positive as the potential increases, indicating that delithiation is progressing. This shows that the nitrogen-doped carbon particles used in the negative electrode half-cell have excellent charge-discharge characteristics.

[0096] FIG. 8(a) is a graph showing the measurement results of current values ​​when cyclic voltammetry of the negative electrode half cell obtained above was examined at voltages of 0.1 V / s, 0.3 V / s, 0.5 V / s, 0.7 V / s, or 1.0 V / s.

[0097] In Fig. 8(a), A to E are graphs showing the measurement results of the current value when voltages of 0.1 V / s, 0.3 V / s, 0.5 V / s, 0.7 V / s, and 1.0 V / s are applied, respectively. Fig. 8(b) is a graph showing the relationship between the scan rate and the peak current in the cyclic voltammetry of the negative electrode half cell.

[0098] The peak current is calculated by the formula: Ip=2.69×10 5 ×n 3 / 2 ×A×D Li 1 / 2 ×C Li ×V 1 / 2 (where Ip is the peak current (A), n is the equivalent of lithium ion / mol, and A is the electrode area (cm 2 ), D Li is the diffusion coefficient (cm 2 / s), C Li is the lithium ion concentration (mol / cm 3 ), V indicates the scan speed (V / s) It can be calculated using the Randles-Sevcik formula:

[0099] When the lithium ion diffusion coefficient was examined based on the Randles-Sevcik equation, the lithium ion diffusion coefficient was found to be 1.11×10 -8 cm 2This shows that the negative electrode half cell obtained above has excellent diffusibility (mobility) of lithium ions.

[0100] [Charge and discharge of negative electrode half-cell] The negative electrode half cell obtained above was repeatedly charged and discharged. The results are shown in Figure 9. In Figure 9, A is a graph showing the relationship between the number of times the negative electrode half cell was charged and discharged and the discharge capacity, and B is a graph showing the relationship between the number of times the negative electrode half cell was charged and discharged and the charge / discharge efficiency (Coulomb efficiency).

[0101] As shown in the graph of FIG. 9, which shows the relationship between the number of charge / discharge cycles and the discharge capacity of the negative electrode half-cell, the discharge capacity of the negative electrode half-cell obtained above was approximately 180 mA h / g or more even after 1,300 cycles. This shows that the charge / discharge durability (cycle characteristics) is significantly superior, at least twice as much as that of a conventional negative electrode using carbon as the electrolyte, which had a charge / discharge durability (cycle characteristics) of at most 500 cycles.

[0102] In addition, the discharge capacity of the negative electrode half cell obtained above was constant at a Coulombic efficiency of about 100% even after 1,300 charge / discharge cycles, indicating that the quality is stable and the durability is excellent.

[0103] [Fast charging performance] The negative electrode half cell obtained above was used to examine the time required for charging by changing the charging current. The results are shown in Table 2.

[0104] [Table 2]

[0105] The results shown in Table 2 show that when the charging current was about 2.86 mA / g, the charging capacity of the negative electrode half-cell obtained above was maintained at 115 mA h / g or more even after 1,000 charge / discharge cycles, and the negative electrode half-cell could be charged in a short time of about 10 minutes.

[0106] Therefore, since the lithium ion secondary battery of the present invention has a high discharge capacity, excellent durability against charging and discharging, and high-speed charging ability, it is believed that it will contribute to the rapid charging of EVs in short periods of time at places such as service areas on highways. [Industrial Applicability]

[0107] The nitrogen-doped carbon of the present invention, the negative electrode active material for a lithium ion secondary battery containing the nitrogen-doped carbon, and the lithium ion secondary battery having a negative electrode containing the negative electrode active material for a lithium ion secondary battery have a high discharge capacity, excellent durability against charging and discharging, and excellent high-speed charging ability that allows charging in a short time, and are therefore expected to be used in, for example, smartphones, tablet personal computers, hybrid automobiles, electric automobiles, and the like.

Claims

1. A negative electrode active material for a lithium ion secondary battery comprising nitrogen-doped carbon particles having a nitrogen atom content of 15% by mass or more, the nitrogen-doped carbon particles being made of a compound represented by the formula: 【Chemistry 1】 and a number average molecular weight of 2,000 to 100,000 is used, and the polybenzimidazole is calcined to contain nitrogen-doped carbon particles composed of carbon atoms, nitrogen atoms, and oxygen atoms.

2. The nitrogen doped carbon particles are coated with a compound of formula (Ia): 【Chemistry 2】 A compound represented by formula (Ib): 【Chemistry 3】 pyridine represented by formula (Ic): 【Chemistry 4】 and pyrrole represented by formula (Id): 【Chemistry 5】 2. The negative electrode active material for a lithium ion secondary battery according to claim 1, comprising an oxygen atom-containing pyridine compound represented by the formula:

3. 3. The negative electrode active material for a lithium ion secondary battery according to claim 1, wherein the spacing between crystal planes of the nitrogen-doped carbon particles is 0.35 to 0.37 nm.

4. A lithium ion secondary battery having a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode, the negative electrode comprising the negative electrode active material for lithium ion secondary batteries according to claim 3.

Citation Information

Patent Citations

  • Nonaqueous electrolyte energy storage device

    JP1988216272A

  • Carbon material and its production as well as nonaqueous electrolytic battery and its production

    JP2001080914A

  • Nitrogen-containing carbon and method of manufacturing the same

    JP2005239456A

  • Method for producing monolithic porous carbon discs from aromatic organic precursors

    JP2008509876A

  • Carbon material and method for producing the same

    JP2011006280A